Perceived Value and Perceived Quality on Repurchase Intention: The Case Study Of Spotify in Bandung - Tarmidi, Didi; Santoso, Anton Budi; Marinda, Vina Silviani; Amalia, Shendy (STKIP Yapis Dompu, 2022)
The rapid development of digital music applications in Indonesia is an opportunity for digital music application providers to meet the needs and desires of the community. One of them is the Spotify app. The problem is based on the number of Spotify Freemium users than Spotify Premium and the start of many new digital music applications that are starting to emerge, this is a challenge for Spotify is increasing its repurchase intention. The research method used in this study is a quantitative method with a descriptive type of research. Sampling was carried out using a non-probability sampling technique used was purposive sampling with a total of 400 respondents using the Spotify application in Bandung City. Meanwhile, the data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results of the study based on descriptive analysis for the perceived value variable are already in the excellent category by 89%, the perceived quality variable is already in the excellent category by 88%, and the intention repurchase variable is already in the excellent category by 89%. Perceived value and perceived quality have a positive and significant effect on repurchase intention with a magnitude of influence of 48.1% and the remaining 51.9% influenced by other factors that were not studied.